GPT-4 in Radiology: Improvements in Advanced Reasoning - Bhayana, Rajesh; Bleakney, Robert R; Krishna, Satheesh (Radiology, 2023)
Supplemental material is available for this article. See also the article by Bhayana et al and the editorial by Lourenco et al in this issue.Supplemental material is available for this article. See also the article by Bhayana et al and the editorial by Lourenco et al in this issue.